Animal models in chronic obstructive pulmonary disease-an overview - Marcelino, Monica Yonashiro; Fuoco, Natalia Langenfeld; Faria, Carolina Arruda de; Kozma, Rodrigo de Las Heras; Marques, Lais Fernanda [UNESP]; Ribeiro-Paes, Joao Tadeu [UNESP] (Informa Healthcare, 2014)
Chronic obstructive pulmonary disease (COPD) is characterized by progressive airway obstruction resultant from an augmented inflammatory response of the respiratory tract to noxious particles and gases. Previous reports present a number of different hypotheses about the etiology and pathophysiology of COPD. The generating mechanisms of the disease are subject of much speculation, and a series of questions and controversies among experts still remain. In this context, several experimental models have been proposed in order to broaden the knowledge on the pathophysiological characteristics of the disease, as well as the search for new therapeutic approaches for acute or chronically injured lung tissue. This review aims to present the main experimental models of COPD, more specifically emphysema, as well as to describe the main characteristics, advantages, disadvantages, possibilities of application, and potential contribution of each of these models for the knowledge on the pathophysiological aspects and to test new treatment options for obstructive lung diseases.
Keywords: animal model; chronic obstructive pulmonary disease; emphysema